2016
DOI: 10.5130/ajceb.v16i1.4818
|View full text |Cite
|
Sign up to set email alerts
|

On the external validity of construction bidding experiment

Abstract: The external validity of experimental studies and in particular, the subject pool effects have been much debated among researchers. The common objections are that the use of student as experimental subjects is invalid as they are likely to be unrepresentative. This paper addresses this methodological aspect in building economics research. It compares the bidding behavioural patterns of experienced construction executives (professionals) and student subjects through replication of a bidding experiment that aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The subjects submitted rationale bids that support the use student subjects in similar studies testing theories as advocated in Oo (2016). Together with the groups of experimental studies on information feedback in construction bidding that used student subjects as highlighted in the above review, the robust findings in this study should lead to more confidence in the use of experimental approaches in building economics research.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The subjects submitted rationale bids that support the use student subjects in similar studies testing theories as advocated in Oo (2016). Together with the groups of experimental studies on information feedback in construction bidding that used student subjects as highlighted in the above review, the robust findings in this study should lead to more confidence in the use of experimental approaches in building economics research.…”
Section: Discussionmentioning
confidence: 91%
“…These findings provide evidence on the robustness of experimental results in building economics research that used student subjects, and similarly in this study where student subjects were used. Although Oo's (2016) study is the only study hitherto that examined external validity of experimental studies in building economics research, this problem has been much debated in the social sciences of which building economics and construction bidding research are parts. In defending the external validity of experimental studies, many authors have concluded that field and laboratory results are highly complementary, and that both are important to the progress of knowledge in social sciences (e.g., Levitt and List 2007, Falk and Heckman 2009, Kessler and Vesterlund 2015, and this is true also for building economics and construction bidding research (Oo 2016).…”
Section: Field and Experimental Findingsmentioning
confidence: 99%
See 2 more Smart Citations